Improved conductivity and capacitance of interdigital carbon microelectrodes through integration with carbon nanotubes for micro-supercapacitors - Yang, Yanjuan; He, Liang; Tang, Chunjuan; Hu, Ping; Hong, Xufeng; Yan, Mengyu; Dong, Yixiao; Tian, Xiaocong; Wei, Qiulong; Mai, Liqiang (Nano research, 2016)
In the last decade, pyrolyzed-carbon-based composites have attracted much attention for their applications in micro-supercapacitors. Although various methods have been investigated to improve the performance of pyrolyzed carbons, such as conductivity, energy storage density and cycling performance, effective methods for the integration and mass-production of pyrolyzed-carbon- based composites on a large scale are lacking. Here, we report the development of an optimized photolithographic technique for the fine micropatterning of photoresist/chitosan-coated carbon nanotube （CHIT-CNT） composite. After subsequent pyrolysis, the fabricated carbon/CHIT-CNT microelectrode-based micro-supercapacitor has a high capacitance （6.09 mF.cm-2） and energy density （4.5 mWh.cm-3） at a scan rate of 10 mV.s-L Additionally, the micro-supercapacitor has a remarkable long-term cyclability, with 99.9% capacitance retention after 10,000 cyclic voltammetry cycles. This design and microfabrication process allow the application of carbon microelectromechanical system （C-MEMS）-based micro-supercapacitors due to their high potential for enhancing the mechanical and electrochemical performance of micro-supercapacitors.